Output energy distribution potential enabled by a nanofluid-assisted hybrid generator. (15th February 2023) - Hong, Wenpeng; Li, Boyu; Li, Haoran; Zi, Junliang
Abstract: Beam splitting is an accessible approach for the thermal decoupling of photovoltaic (PV) and photothermal (PT) modules. Generally, recovering the thermal energy enables us to enhance the high-grade power output via a thermoelectric generator (TEG). However, PV/T systems with thin-film filters are in despair of stability and efficiency. Herein, we introduce a hybrid electricity generator integrating PV generation, waste heat power generation, and residual heat storage with the assistance of a liquid beam splitter (LBS). The unavailable solar energy for the PV cell will be absorbed by the nanofluid in the LBS, and transferred to the hot junction of the TEG. Moreover, the residual heat flows back to the heat storage tank and re-enters the LBS. For this strategy, the current density of the TEG exceeds 50% of the total output electricity and relatively increases by ∼2.55 times if the cooling temperature decreases from 25 to 5 °C. Importantly, the hybrid device not only responds quickly to the change in operating conditions but has great potential to resist solar energy fluctuation. This novel hybrid electricity generator is expected to promote the development of sustainable solar power generation technology, especially in cold regions. Graphical abstract: Image 1 Highlights: A hybrid electricity generator assisted with a nanofluid filter was developed. The nanofluid was expected to overcome the sharp fluctuation of the energy output. The current density of the TEG module exceeded 50% of the total electricity. The performance of the hybrid system was more suitable for cold regions.